GENDER DIFFERENCES IN COMPLIMENT STRATEGIES IN SOCIAL MEDIA INTERACTION - Nisjatul Miranda; Hamzah Hamzah (Universitas Negeri Padang, 2018)
Compliment is a form of positive speech that is intended as a form to respect or appreciate something. In giving compliment a person has a certain options. This paper investigated the compliment strategies employed by male and female in social media interaction. This research is categorized as documentaries studysince the object of this research was in form of documentation of compliment use in column comment of Facebook.This research uses qualitative and quantitative methods. Finding showed that in different gender, male give more explicit compliment (94.4%) than female (93.3%). For the second strategy of compliment (implicit compliment), female tend to use implicit compliment (6.7%) than male (3.7%). In the last strategy of compliment (non-compliment), male prefer to use that strategy 1 time (1.8%) but female choose not to use non-compliment. In the same gender, female give more explicit compliment (1.8%) than male (0%). However, female also use implicit compliment 1 time but male get zero. For non-compliment strategy, male and female choose not to use that strategy in giving compliment.